Biostatistics a computing approach - Anderson, Stewart, 1955- (Chapman & Hall/CRC biostatistics series., 2012)
""The book presents important topics in biostatistics alongside examples provided in the programming languages SAS and R. ... The book covers many relevant topics every student should know in a way that it makes it easy to follow ... each chapter provides exercises encouraging the reader to deepen her/his understanding. I really like that the theory is presented in a clear manner without interruptions of example programs. Instead, the programs are always presented at the end of a section. ... this book can serve as a good start for the more statistics inclined students who haven't yet recognized tha.